Effect of sandwich bone augmentation using hydroxyapatite and demineralized freeze- dried bone on infrabony pocket treatment - Eka Pramudita Ramadhany; Al Sri Koes Soesilowati; Sri Pramestri Lastianny (Faculty of Dentistry, Universitas Gadjah Mada, 2019)
Periodontitis is periodontal inflammation in response to plaque bacterial antigens, causing damage to periodontal ligament and alveolar bone resorption. Bone graft material combination i.e. demineralized freeze-dried bone allograft (DFDBA) and hydroxyapatite (HA) using sandwich bone augmentation (SBA) method will support each other and will be beneficial to be used as a scaffold. The body takes long time to resorb HA so this could complement DFDBA which is more easily dissolved. This study aimed to reveal the effect of bone graft addition using SBA method on the treatment of infrabony pocket with open flap debridement in terms of probing depth, relative attachment loss, alveolar bone height, and density. This study was carried out to 20 infrabony pockets, where 10 of them were treated using open flap debridement with HA addition, while the other 10 groups were treated using open flap debridement with DFDBA and HA using SBA method. Probing depth and relative attachment loss were measured on days 0, 30 and 90. Bone height and density were measured using cone-beam computed tomography (images on day 0 and 90). The study showed that probing depth reduction on SBA group was greater than HA group. There were significant differences in probing depth and relative attachment loss examinations. However, bone height and bone density reduction did not show any significant difference. The conclusion from this study is open flap debridement using SBA method yields better regeneration in terms of probing depth and relative attachment loss than open flap debridement with HA addition. There is no difference in bone height and bone density between the two groups.